2019 ARIA Care pathways for allergen immunotherapy. Issue 11 (15th July 2019) - Bousquet, Jean; Pfaar, Oliver; Togias, Alkis; Schünemann, Holger J.; Ansotegui, Ignacio; Papadopoulos, Nikolaos G.; Tsiligianni, Ioanna; Agache, Ioana; Anto, Josep M.; Bachert, Claus; Bedbrook, Anna; Bergmann, Karl‐Christian; et al.
Abstract: Allergen immunotherapy (AIT) is a proven therapeutic option for the treatment of allergic rhinitis and/or asthma. Many guidelines or national practice guidelines have been produced but the evidence‐based method varies, many are complex and none propose care pathways. This paper reviews care pathways for AIT using strict criteria and provides simple recommendations that can be used by all stakeholders including healthcare professionals. The decision to prescribe AIT for the patient should be individualized and based on the relevance of the allergens, the persistence of symptoms despite appropriate medications according to guidelines as well as the availability of good‐quality and efficacious extracts. Allergen extracts cannot be regarded as generics. Immunotherapy is selected by specialists for stratified patients. There are no currently available validated biomarkers that can predict AIT success. In adolescents and adults, AIT should be reserved for patients with moderate/severe rhinitis or for those with moderate asthma who, despite appropriate pharmacotherapy and adherence, continue to exhibit exacerbations that appear to be related to allergen exposure, except in some specific cases. Immunotherapy may be even more advantageous in patients with multimorbidity. In children, AIT may prevent asthma onset in patients with rhinitis. mHealth tools are promising for the stratification and follow‐up of patients.